The Inessential Project, The Essential Realm: The Original Research Spectrality of the World, The Spectrality of the Human - Mohammad Taghi Iman; Ali Bandarrigizadeh (حکمت و فلسفه, 2022)
The ideas that have been fixed in a human’s mind, and the abstract realm of his life, in addition to its concrete realm is under their extensive and deep affections, are ideas whose spectrality is manifested in Stirner’s formulation of the human world. Despite encompassing thesecharacteristics, which are the characteristics of the essential, the specters of ideas are open to presenting an inessential project. Such this project, which is based on disclosing a conceptual binary in Deleuze’s philosophical system, discloses a philosophical reading which manifests the spectrality of idea as a basis for the essentiality of a certain sphere that “human” conceptual signifier constructs. This Stirnerean reading reveals that such a sphere is the non-pluralistic embodiment of its constituent elements.